2021
DOI: 10.1007/s10668-021-02059-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural perspective on sustainable consumption: implications for consumer motivations and promotion

Abstract: Firms in the past have based their marketing and promotion strategies on the assumption of infinite resources and zero environmental impact. With the growing importance of environmental costs associated with finite resources, firms need to revisit their marketing and promotion strategies. This study defines and conceptualizes horizontal/vertical individualism–collectivism (H/V I-C) cultural value orientations as antecedents of sustainable consumption. Drawing on H/V I-C value orientations, this study attempts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 126 publications
(263 reference statements)
0
22
0
Order By: Relevance
“…It is assumed that there are differences when considering the various methodological aspects of each research, which, to some extent, may mean the creation of a measurement scale adaptable to different contexts to achieve results that are easier to contrast consistently. In parallel, the importance of cross-cultural research stands out, demonstrating the relevance and consistency of this variable [40,87,91,105,107] since it achieves different results despite the similarity in the methodological instrument.…”
Section: Inconsistencies and Difficulties Of The Sustainable Consumer...mentioning
confidence: 98%
See 1 more Smart Citation
“…It is assumed that there are differences when considering the various methodological aspects of each research, which, to some extent, may mean the creation of a measurement scale adaptable to different contexts to achieve results that are easier to contrast consistently. In parallel, the importance of cross-cultural research stands out, demonstrating the relevance and consistency of this variable [40,87,91,105,107] since it achieves different results despite the similarity in the methodological instrument.…”
Section: Inconsistencies and Difficulties Of The Sustainable Consumer...mentioning
confidence: 98%
“…[89] agrees with this by mentioning that there are at least 80 theories of behavior in different sciences of the subject (sociology, anthropology, psychology, and economics). This affirmation can be sustained by knowing the enormous amount of variables that affect the sustainable behavior of subjects, among which are: gender [6,15,[90][91][92], age [6], personality [48,[93][94][95][96], income [83,92,[97][98][99], access to information and analytical skills [2,38,82,100], family [54,101], society and its agents [55,56,79,81,102,103], technology and digital opinion [87,104], values [83], culture [3,67,[105][106][107], marketing initiatives [48], religion [52,53], physical activity [108], or crises, such as the COVID-19 pandemic [15,20,22], to mention a few. It highlights how even aspects linked to the perception of masculinity (o...…”
Section: The Complexity Of "Being" a Sustainable Consumermentioning
confidence: 99%
“…Marketing that resonates with these values and norms can more effectively motivate consumers to choose sustainable energy. Campaigns highlighting the social benefits of renewable energy, such as contributing to community well-being and protecting future generations, can tap into these values, fostering a sense of collective responsibility and action toward sustainability [178][179][180] . Despite the potential of sustainable energy marketing to influence customer behavior, there are barriers and challenges to consider.…”
Section: Sustainable Marketing Practices Of Energy Companiesmentioning
confidence: 99%
“…Almeida and Coelho (2019) suggested that diverse cultural values and social norms contribute highly to these changes. Studies have shown that cultural dissimilarities can influence individuals' persuading processes, behaviors, actions, and interests (Smith et al, 2013; Ur Rahman et al, 2023). Consequently, assessing passengers' insights of CSR across countries helps understand why CSR may have a greater impact on passenger conduct/satisfaction in some cultures compared with others.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%